PENGARUH PENDAPATAN, EDUKASI DAN RELIGIUSITAS TERHADAP MINAT MUZAKKI DALAM MEMBAYAR ZAKAT PROFESI DI BAZNAS KOTA TANGERANG - Ikhwannusofa, Muhammad; Ichsan, Nurul (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2023)
This study aims to analyze the factors that influence the interest of muzakki in paying professional zakat at BAZNAS Tangerang City. The independent variables in this study are income, education and religiosity and the dependent variable is the interest of muzakki in paying zakat. The population in this study is the muzakki of BAZNAS Tangerang City, with a total sample of 100 respondents. The sampling technique used was non-probability sampling with accidental sampling or convenience sampling. The data used was obtained by distributing questionnaires through google form. The results showed that there was a positive and significant influence between each variable, namely income (X1) with a value of 0.315, education (X2) with a value of 0.168 and religiosity (X3) with a value of 0.219 on muzakki's interest in paying zakat (Y).